(untitled) (Majalah Kedokteran Bandung, 2026)
Intrahepatic and gallbladder ascariasis complicated by liver abscess is an exceptionally rare clinical condition that presents significant diagnostic and therapeutic challenges. The migration of Ascaris lumbricoides into the biliary system is uncommon due to the narrow and tortuous anatomy of the cystic duct and intrahepatic bile ducts. When it occurs, it may lead to complications such as acalculous cholecystitis and liver abscess. This case report discussed a case of a 25-year-old male presenting with a one-week history of abdominal pain, fever, diarrhea, vomiting, dehydration, pale appearance, and general weakness. Physical examination revealed decreased skin turgor and tenderness in the right upper abdomen with no palpable hepatosplenomegaly. Abdominal ultrasonography and multi-slice computed tomography (MSCT) showed the presence of liver abscesses and intrahepatic Ascaris lumbricoides. The patient underwent laparoscopic cholecystectomy and abscess drainage, followed by metronidazole therapy and supportive treatment. Postoperative ultrasonography on Day 14 showed complete resolution of the infection with no remaining worms. This case underscores the importance of considering biliary ascariasis in patients presenting with non-specific gastrointestinal symptoms. Prompt imaging with USG and MSCT plays a vital role in early diagnosis, while laparoscopic cholecystectomy combined with liver abscess drainage is a safe and effective therapeutic approach.